Penguatan Rantai Nilai Halal bagi UMKM: Alih Pengetahuan dari Model Rantai Nilai Halal Indonesia - Nurlela Nurlela; Darmawati Darmawati; Ahmad Fauzul Hakim Hasibuan; Iswadi Bensaadi (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2026)
This community engagement program aims to strengthen the halal value chain of micro, small, and medium enterprises (MSMEs) in Hagu Selatan Village, Banda Sakti District, Lhokseumawe City through knowledge transfer based on the Indonesian halal value chain model. MSMEs play a vital role in regional economic development, yet many still face challenges in understanding halal–thayyiban principles, fulfilling certification requirements, managing production processes, and accessing Islamic financing. Limited adoption of digitalization also reduces their competitiveness in the rapidly growing halal industry. The program applies a participatory approach by involving universities, village authorities, and MSMEs. Key activities include needs assessment, training on halal value chain concepts, technical assistance for halal certification documents, workshops on digital business practices, and business clinics on Islamic financing. A Halal Value Chain Learning Circle is also established to support continuous collaboration and knowledge sharing. The program is expected to enhance MSME capacity, improve product quality, expand market access, and contribute to a sustainable halal ecosystem in Aceh.